Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2147/ott.s170854
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic translation initiation factor 3 subunit G (EI F3G) resensitized HC T116/5-Fu to 5-fluorouracil (5-Fu) via inhibition of MRP and MDR1

Abstract: PurposeColorectal cancer (CRC) has become a predominant cancer and accounts for approximately 10% of cancer-related mortality. Drug resistance still remains a priority mortality factor for patients due to no available therapeutic alternatives. The purpose of the present study was to investigate the underlying molecular mechanisms how eukaryotic translation initiation factor 3 subunit G (EIF3G) resensitized 5-Fu-resistant human CRC cells (HCT116/5-Fu) to 5-fluorouracil (5-Fu).MethodsMultiple cellular and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A study revealed that the eIF3, central to protein synthesis initiation, can influence autophagy by controlling the translation of proteins in this process ( 151 ). Specifically, the eukaryotic translation initiation factor 3 subunit G (EIF3G) is implicated in the progression of human colorectal cancer ( 152 ). Functional assays revealed that EIF3G overexpression enhances HCT-116 cell proliferation, migration, and xenograft tumor growth, whereas xenograft tumors derived from EIF3G-silenced HCT116 cells exhibited reduced weights and volumes compared to those from control cells ( 151 ).…”
Section: M6a Methylation In Autophagy Regulationmentioning
confidence: 99%
“…A study revealed that the eIF3, central to protein synthesis initiation, can influence autophagy by controlling the translation of proteins in this process ( 151 ). Specifically, the eukaryotic translation initiation factor 3 subunit G (EIF3G) is implicated in the progression of human colorectal cancer ( 152 ). Functional assays revealed that EIF3G overexpression enhances HCT-116 cell proliferation, migration, and xenograft tumor growth, whereas xenograft tumors derived from EIF3G-silenced HCT116 cells exhibited reduced weights and volumes compared to those from control cells ( 151 ).…”
Section: M6a Methylation In Autophagy Regulationmentioning
confidence: 99%
“…It is downregulated in cancers exemplified in melanoma, lung cancer and pancreatic cancer ( 53 ). A study showed that eIF3g is a targeted regulator of CRC chemotherapeutic resistance ( 54 ). A variant of eIF3h (rs16892766) was discovered to be associated with higher CRC risk ( 55 ).…”
Section: Eukaryotic Translation Initiation Factorsmentioning
confidence: 99%